Qur'an Communication in the Makkiyah and Madaniyah Phases: Changes in Da'wah Style and Strategy - Ibnu Muchlis (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Qur'an as the primary source of Islamic teachings contains not only theological messages but also dynamic communication strategies that evolved according to the socio-historical context of revelation. This article examines the characteristics of Qur'anic communication during the Makkan and Madinan phases, emphasizing changes in linguistic style, thematic focus, and da'wah strategies. This study employs a qualitative approach through library research and thematic analysis of Makkan and Madinan verses based on classical and contemporary tafsir literature. The findings indicate that Makkan communication is persuasive and emotional, focusing on strengthening monotheism and individual morality, while Madinan communication is normative and argumentative, oriented toward establishing social order and legal regulations for the Muslim community. This shift demonstrates the adaptability of Qur'anic da'wah communication and its relevance to contemporary Islamic communication studies.